Overview of Academic Self-Efficacy in Students Working at the Surabaya Pharmacy Academy: Gambaran Efikasi Diri Akademik pada Mahasiswa yang Bekerja di Akademi Farmasi Surabaya - Mentari, Ayu Yulia; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the academic self-efficacy of pharmacy academy students. This research uses descriptive quantitative method. The sample used is the Surabaya Pharmacy Academy students who work with a total of 100 students. The sampling method used in this research is saturated sampling. The data collection method used a Likert scale, namely the academic self-efficacy scale. The results of data analysis from this study were in the moderate category of academic self-efficacy. The results of further research that the percentage of high academic self-efficacy aspects is the state aspect in completing the task.